Impact of foreign labour on labour productivity and output growth in Malaysian manufacturing sector. - Isa, Noraini (2011)
The growing presence of foreign labours in Malaysia can be explained by excess demand for cheap labour due to rapid economic growth and industrialization. Consequently, when the foreign labours flux a country, it becomes necessary that their impact towards productivity and output in this country be analysed. Thus, this study determines the impact of foreign labours on labour productivity as well as their effect on output growth in Malaysian manufacturing sector. The Cobb-Douglas production function is used to derive the model specification in this study. The results in this study showed that foreign labours have positive and significant impact on labour productivity. Foreign labours also have positive influence on output growth in Malaysian manufacturing sector. Furthermore, the study also revealed that foreign labours are complements to domestic labours. Comment [d1]: Is this true